Systemic Delivery of an Adjuvant CXCR4-CXCL12 Signaling Inhibitor Encapsulated in Synthetic Protein Nanoparticles for Glioma Immunotherapy - Alghamri, Mahmoud S. (2022)
Glioblastoma (GBM) is an aggressive primary brain cancer, with a 5 year survival of ∼5%. Challenges that hamper GBM therapeutic efficacy include (i) tumor heterogeneity, (ii) treatment resistance, (iii) immunosuppressive tumor microenvironment (TME), and (iv) the blood-brain barrier (BBB). The C-X-C motif chemokine ligand-12/C-X-C motif chemokine receptor-4 (CXCL12/CXCR4) signaling pathway is activated in GBM and is associated with tumor progression. Although the CXCR4 antagonist (AMD3100) has been proposed as an attractive anti-GBM therapeutic target, it has poor pharmacokinetic properties, and unfavorable bioavailability has hampered its clinical implementation. Thus, we developed synthetic protein nanoparticles (SPNPs) coated with the transcytotic peptide iRGD (AMD3100-SPNPs) to target the CXCL2/CXCR4 pathway in GBM via systemic delivery. We showed that AMD3100-SPNPs block CXCL12/CXCR4 signaling in three mouse and human GBM cell cultures in vitro and in a GBM mouse model in vivo. This results in (i) inhibition of GBM proliferation, (ii) reduced infiltration of CXCR4+ monocytic myeloid-derived suppressor cells (M-MDSCs) into the TME, (iii) restoration of BBB integrity, and (iv) induction of immunogenic cell death (ICD), sensitizing the tumor to radiotherapy and leading to anti-GBM immunity. Additionally, we showed that combining AMD3100-SPNPs with radiation led to long-term survival, with ∼60% of GBM tumor-bearing mice remaining tumor free after rechallenging with a second GBM in the contralateral hemisphere. This was due to a sustained anti-GBM immunological memory response that prevented tumor recurrence without additional treatment. In view of the potent ICD induction and reprogrammed tumor microenvironment, this SPNP-mediated strategy has a significant clinical translation applicability.